2014
DOI: 10.1016/j.brat.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of change in emotion regulation and social anxiety during cognitive-behavioral therapy for social anxiety disorder

Abstract: Cognitive-behavioral therapy (CBT) for social anxiety disorder (SAD) may decrease social anxiety by training emotion regulation skills. This randomized controlled trial of CBT for SAD examined changes in weekly frequency and success of cognitive reappraisal and expressive suppression, as well as weekly intensity of social anxiety among patients receiving 16 weekly sessions of individual CBT. We expected these variables to (1) differ from pre-to-post-CBT vs. Waitlist, (2) have differential trajectories during C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 55 publications
6
52
0
1
Order By: Relevance
“…This shows that training emotion regulation strategies are effective on reappraisal as a positive and adaptive emotion regulation strategy. The findings and conclusions of this research were in line with the results of previous studies (Ghaednia, 2013;Goldin et al, 2014). Goldin et al (2014) conducted a study among people suffering from social anxiety disorder.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This shows that training emotion regulation strategies are effective on reappraisal as a positive and adaptive emotion regulation strategy. The findings and conclusions of this research were in line with the results of previous studies (Ghaednia, 2013;Goldin et al, 2014). Goldin et al (2014) conducted a study among people suffering from social anxiety disorder.…”
Section: Discussionsupporting
confidence: 90%
“…The findings and conclusions of this research were in line with the results of previous studies (Ghaednia, 2013;Goldin et al, 2014). Goldin et al (2014) conducted a study among people suffering from social anxiety disorder. They found that training emotion regulation skills helped to decrease the signs and symptoms of social anxiety and shyness in people with anxiety disorder.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations